Electronic Court (e-court) at the Sarolangun Religious Court - Masriyani, Masriyani; Tresya, Tresya; Siregar, Nella Octaviany; Ibrahim, Muhammad Roihan (Information Technology and Science (ITScience), 2024)
This research aims to analyze the E-Court justice system at the Sarolangun Religious Court, using empirical juridical research methods, which prioritize field data as main data and library materials as supporting data. Data collection techniques are carried out through interviews and literature studies of the data needed in the analysis process. The results of this research are a description of the implementation of the E-Court system at the Sarolangun Religious Court and an analysis of inhibiting factors and opportunities for its development. From the description of the discussion, it can be concluded that the implementation of the system is not yet fully effective and is less popular with users, this is because the understanding of the e-court system is not yet fully understood by users. And it is constrained by application systems that use the internet network, so network factors also influence the e-court system process.